When smoke comes to town: The impact of biomass burning smoke on air quality. (November 2015) - Keywood, Melita; Cope, Martin; Meyer, C.P. Mick; Iinuma, Yoshi; Emmerson, Kathryn
Abstract: Biomass burning aerosols influence the radiative balance of the earth-atmosphere system. They also reduce visibility and impact human health. In addition, trace gases and aerosols emitted to the atmosphere during large biomass burning episodes may have a significant effect on atmospheric chemistry due to the presence of reactive species. Six hundred and ninety wildfires burned more than one million hectares in Victoria, Australia between December 2006 and February 2007. Thick smoke haze was transported to Melbourne (population 3.9 million) on several occasions, causing PM10 (particulate mass less than 10 μm in diameter) concentrations to exceed 200 μg m −3 . The presence of elevated total secondary organic aerosol (SOA) and speciated SOA compounds (including pinene and cineole oxidation products), O3, and the larger aerosol mode diameter during smoke impacted periods indicated the presence of photochemical oxidation within the plume. The presence of organosulfate compounds and nitro-oxy organosulfate compounds indicated oxidation may have occurred in the presence of acidic seed aerosol and that oxidation may also have occurred at night. Older smoke plumes (aged 30 h) displayed higher concentrations of a number of gaseous and aerosol species relative to the younger smoke plumes (aged 3 h). SOA compounds made up a greater fraction of speciated organic mass in the old plume than in the young plume where speciated biomass burning compounds dominated. Cineole oxidation products made up a greater fraction of the speciated SOA compounds in the old plume while pinene oxidation products made up a greater fraction of the total SOA speciated mass in the samples from the young plume. This may be a result of the slower reaction rate of cineole with OH. Organosulfate compounds and nitro-oxy organosulfate compounds made up greater fractions of the speciated SOA mass in the old plume consistent with the production of nitro-oxy organosulfate compounds under night time conditions in the presence of acidic seed. These results suggest that enhanced photochemical activity occurs in smoke plumes and can significantly change the composition and microphysical properties of aerosol, potentially leading to changes in the optical and thus radiative properties of the aerosol. Highlights: Plumes that impacted Aspendale resulted in elevated concentrations of particles and gases. Old plumes showed evidence of more photochemistry than young plumes. Speciated SOA compounds made up a greater fraction of speciated organic mass old plumes. Speciated biomass burning compounds dominated the speciated organic mass in the young plumes. Smoke plumes resulted in elevated concentrations of particles and gases.